Short-term outcome of treatment limitation discussions for newborn infants, a multicentre prospective observational cohort study. Issue 2 (15th November 2016) - Aladangady, Narendra; Shaw, Chloe; Gallagher, Katie; Stokoe, Elizabeth; Marlow, Neil; ,
Abstract : Objective: To determine the short-term outcomes of babies for whom clinicians or parents discussed the limitation of life-sustaining treatment (LST). Design: Prospective multicentre observational study. Setting: Two level 3, six level 2 and one level 1 neonatal units in the North-East London Neonatal Network. Participants: A total of 87 babies including 68 for whom limiting LST was discussed with parents and 19 babies died without discussion of limiting LST in the labour ward or neonatal unit. Outcome measures: Final decision reached after discussions about limiting LST and neonatal unit outcomes (death or survived to discharge) for babies. Results: Withdrawing LST, withholding LST and do not resuscitate (DNR) order was discussed with 48, 16 and 4 parents, respectively. In 49/68 (72%) cases decisions occurred in level 3 and 19 cases in level 2 units. Following the initial discussions, 34/68 parents made the decision to continue LST. In 33/68 cases, a second opinion was obtained. The parents of 14/48 and 2/16 babies did not agree to withdraw and withhold LST, respectively. Forty-seven out of 87 babies (54%) died following limitation of LST, 28/87 (32%) died receiving full intensive care support, 5/87 (6%) survived following a decision to limit LST and 7/87 (8%) babies survived following decision to continue LST. Conclusions: A significant proportion of parents chose to continue treatment following discussions regarding limiting LST for their babies, and a proportion of these babies survived to neonatal unit discharge. The long-term outcomes of babies who survive following limiting LST discussion need to be investigated.